Low rate of RNAemia in blood donations collected during the first wave of COVID‐19 in France. Issue 3 (9th February 2022) - Le Cam, Sophie; Gallian, Pierre; Ricard, Céline; Narboux, Céline; Barlet, Valérie; Maugard, Claude; Hauser, Lisette; Brisbarre, Nadège; Cappy, Pierre; Pillonel, Josiane; Laperche, Syria; Morel, Pascal
Abstract: Background: To investigate the transmission of SARS‐CoV‐2 via blood, we conducted retrospective molecular screening in blood donated during the first pandemic peak in the two French regions with the highest community transmission. Methods: Archived plasma samples randomly selected from donations collected between March 23 and 29, 2020, in Eastern and Northern regions of France were tested for SARS‐CoV‐2 RNA in minipools of 4 donations (MP4) using the Grifols ProcleixSARS‐CoV‐2 assay. Reactive MP4 and the four corresponding plasmas were further tested with alternative RT‐PCRs and sequencing. Testing for SARS‐CoV‐2 antibodies and in vitro infectivity in cell culture were also performed. Results: Among the 2818 MP4 (corresponding to 9672 donations) tested for viral RNA, 5 were weakly reactive. Among the 20 plasmas included in these five MP4, one presented low‐level reactivity with RT‐PCRs and Procleix SARS‐CoV‐2 and was confirmed on sequencing. The estimated prevalence was 1.03/10, 000 (95% CI 0–3.1). The 20 plasmas were antibody nonreactive and none of them showed cytopathic effects in cell culture. When recalled, the index‐donor declared having had symptoms compatible with SARS‐CoV‐2 infection a few days after donation. The two immunocompromised recipients transfused with red blood cells and an inactivated pooled platelet product did not develop COVID‐19. Conclusion: Our results indicated a low prevalence of SARS‐CoV‐2 RNA in the plasma of asymptomatic blood donors during the pandemic peak and no evidence of infectivity in vivo and in vitro. The transfusion risk remains theoretical and does not justify the implementation of SARS‐CoV‐2 NAT for blood donations.